If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 3(x + 2) = 6 Reorder the terms: 3x + 3(2 + x) = 6 3x + (2 * 3 + x * 3) = 6 3x + (6 + 3x) = 6 Reorder the terms: 6 + 3x + 3x = 6 Combine like terms: 3x + 3x = 6x 6 + 6x = 6 Add '-6' to each side of the equation. 6 + -6 + 6x = 6 + -6 Combine like terms: 6 + -6 = 0 0 + 6x = 6 + -6 6x = 6 + -6 Combine like terms: 6 + -6 = 0 6x = 0 Solving 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '6'. x = 0 Simplifying x = 0
| 2x=(400/4) | | 14-3y=-7 | | -3k-39=-5(8k-7) | | -6(1+7a)=27 | | 4t(5t-4t)=0 | | 5/2x=0 | | 65ab^3-45a^2b^2=0 | | 16=9x+2-2x | | 5.4x=7.02 | | 5n^2-16n=-3 | | 7x-8=x+7 | | 0.15(x+10)=8x+20 | | 5-2a=5a-2 | | -1(3x+4)-4r=-2(4r-3)+2 | | 2x+5=6x-9 | | x+-2x+4=3 | | 16+5a=56 | | x^2+4x+4y^2=0 | | 6x+14=5x+12 | | 3(m^2+10m+23)=0 | | r^2+3r=10 | | 7a-7+6a=10-4a | | 3x^2+11x-1-x^3=0 | | y=-2(x+3)2+2 | | x/2=20/10 | | 10t+3(1-4t)= | | x-59=-24 | | A=3.14r*2(5) | | 8m=-14-30 | | x^(2/3)e^x | | 6.5x=7.8 | | 16-4=3x+8-6 |